An Integrated Framework for the Development of Green Infrastructure: A Literature Review - Beauchamp, P.; Adamowski, J. (European Journal of Sustainable Development, 2013)
Green infrastructure (GI) has emerged as an active term of reference in projectdevelopment planning. A gap exists in the GI research literature in the form of theabsence of an integrated framework to assist engineering organizations in planning thestart-up of new projects in the context of greening and sustainability. This study attemptsto identify the existing frameworks that propose the development of green projects.The first purpose of this study is to explore the use of fully integrated GI in theengineering design of a modern, new development. A clear sequence of tasks must definethe workflow, leading teamwork. This literature review identifies several differentapproaches and selects four to build a ready-to-use framework of sequenced tasks, whichincludes all the components of water management (rain and drainage, water supply andwastewater).This essay reviews GI literature with a focus on water resources and ecosystem services. Itincludes the methods, tools, and techniques available in different approaches, such as lowimpact development (LID), leadership in energy and environmental design (LEED), theBritish Columbia (BC) guidebook, and the EPA (Environmental Protection Agency)scorecard. It explores different frameworks to start or structure an urban developmentproject.